Measuring language proficiency in Malay first and second language speakers - Lee, Soon Tat (2024)
Measuring language proficiency is essential in linguistics and psycholinguistics research that investigate bilingual language processing (e.g., Fromont et al., 2020; Sarrett et al., 2022; Singh et al., 2022; Tosun & Filipović, 2022) and cognitive control (e.g., Luque & Morgan-Short, 2021; Ning, 2021). Despite often being construed as a moderating variable in bilingual research, there is a great variability in how language proficiency is operationalised and measured (Hulstijn, 2015; Puig-Mayenco et al., 2023; Surrain & Luk, 2019; Treffers-Daller, 2019; Tremblay, 2011). A systematic review on second language acquisition research (Park et al., 2022) revealed that about 58% of the studies estimated second language proficiency using variables that were closely related to language proficiency (e.g., years of instruction, self-rated proficiency). In contrast, only 42% of them assessed language proficiency with a test (e.g., validated vocabulary tests). Despite being shown as a more consistent measure, and importantly, correlated well with other language performances (e.g., Diependaele et al., 2013; Lemhöfer & Broersma, 2012; Wen & van Heuven, 2017b), implementation of language proficiency test is not always feasible because existing language proficiency tests might not be available in understudied languages or could be impractical (e.g., too time-consuming) for experimental settings. For instance, there is currently no freely available quick Malay proficiency test, although there are 377 million Malay speakers in the world.